The British Wheat Act, 1932 - Plummer, Alfred (Quarterly Journal of Economics, 1932)
I. The aim of the Act, 63.— Two corporations set up, 63.— The fixing of the ascertained average price, 65.— The ascertained supply or quota, 66.— The standard price, 67.— Wheat certificates to be issued, 67.— Quota payments, 67.— Imported flour and quota payments, 68.— The Wheat Commission and the Wheat Fund, 68.— II. Criticism of details; growers will receive the subsidy in a circuitous manner, 69.— Regressive nature of the tax upon consumers, 69.— Compulsory purchase of wheat by Flour Millers* Corporation, 70.— Likely to be very favorable to growers, 71.— III. The Act examined as an expression of policy, 72.— Wheat no longer a pivotal crop in Britain, 72.— Wheat-growing and employment, 73.— Encouragement of wheat-growing likely to discourage specialization on other crops, 75.— State aid to British agriculture should be general, 76.— The State should look to the future, not to the past, 76.